Inventory of tontemboan vocabulary as a regional language protection - Karamoy, Olga; Imbang, Dj.; Palit, Anatje (Linguistics and Culture Review, 2021)
Tontemboan is a language spoken in parts of Minahasa and South Minahasa. Tontemboan is one of the regional languages in North Sulawesi. Tontemboan is one of the languages that are endangered if there is no effort in terms of language participation. The threat of extinction of the Tontemboan language triggers actions to keep from extinction, one of which is the inventory of the vocabulary of the language itself. This inventory is done with the aim of getting vocabulary in the language of the area that is focused on reduplication areas with thought if possible can enrich vocabulary Indonesian. In order to obtain a reduplication form in this language, data collection is carried out by library method and continued with the listening method, which is listening to the use of this language in everyday life by speakers of that language. This method is done in more detail using record techniques. In addition to listening to the use of language, there are also face-to-face interviews with speakers by asking or confirming the vocabulary/reduplication obtained. The instrument used in data collection in face-to-face interviews is to use Swadesh’s vocabulary list that has been modified into a dimlication form.